Constant Power Factor Model of DFIG-Based Wind Turbine for Steady State Load Flow Studies - Rudy Gianto (Energies, 2022)
DFIG (Doubly Fed Induction Generator)-based WPP (Wind Power Plant) is the most popular type of wind-driven electric power generation configuration. The main reason for its popularity is that the DFIG system can capture wind energy more optimally than other WPP configurations. Due to the increasing penetration of WPP in power systems, the need to study its impact on power system performance is becoming increasingly important. To enable such a study to be conducted properly, the first and probably the most crucial step is to model all system components (including the WPP). This paper proposes a new steady state model of DFIG-based WPP for load flow analysis. The proposed model is derived based on DFIG power formulas (i.e., DFIG stator and rotor power formulas). The model in the present work is simple and can easily be incorporated into load flow analysis. Representation of the DFIG in both sub-synchronous and super-synchronous conditions can be carried out by using a single mathematical model. Furthermore, since DFIG can be operated at a constant power factor (i.e., unity, leading, or lagging power factor), this important feature is also considered in the proposed model development.